2010
DOI: 10.1608/frj-3.2.157
|View full text |Cite
|
Sign up to set email alerts
|

UV Radiation and Freshwater Zooplankton: Damage, Protection and Recovery

Abstract: While many laboratory and field studies show that zooplankton are negatively affected when exposed to high intensities of ultraviolet radiation (UVR), most studies also indicate that zooplankton are well adapted to cope with large variations in their UVR exposure in the pelagic zone of lakes. The response mechanisms of zooplankton are diverse and efficient and may explain the success and richness of freshwater zooplankton in optically variable waters. While no single behavioural or physiological protection mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 191 publications
(352 reference statements)
1
77
0
Order By: Relevance
“…Cladocerans have several efficient mechanisms to avoid UVR (Hansson et al., 2007; Rautio & Tartarotti, 2010). Here, we have demonstrated that their ability to exhibit different traits to counteract UVR damage is not only species‐specific, but also differs between lineages within the same species but with different evolutionary histories, and that the involved trade‐offs depend on the environment in which the organisms live.…”
Section: Discussionmentioning
confidence: 99%
“…Cladocerans have several efficient mechanisms to avoid UVR (Hansson et al., 2007; Rautio & Tartarotti, 2010). Here, we have demonstrated that their ability to exhibit different traits to counteract UVR damage is not only species‐specific, but also differs between lineages within the same species but with different evolutionary histories, and that the involved trade‐offs depend on the environment in which the organisms live.…”
Section: Discussionmentioning
confidence: 99%
“…The red coloration of copepods is due to carotenoids, a large family of lipid-soluble pigments that are synthesized only in primary producers but may be either accumulated by zooplankton or biologically converted to other carotenoids, notably astaxanthin, which is the primary carotenoid among crustaceans (Matsuno 2001;Andersson et al 2003;Rhodes 2006). Astaxanthin is a powerful antioxidant (McNulty et al 2007) occurring both in free form and esterified with fatty acids or associated with proteins (Cheesman et al 1967;Matsuno 2001).In zooplankton, carotenoid accumulation is a highly variable trait that has been linked to photoprotection against ultraviolet radiation (UVR) in field studies comparing lakes with differential UVR exposure and in experimental studies (Hairston 1976;Moeller et al 2005;Hylander et al 2009;Rautio and Tartarotti 2010;Sommaruga 2010). The underlying mechanism ascribing astaxanthin photoprotection properties involves the quenching of singlet oxygen ( 1 O 2 ) produced during UVR exposure rather than direct absorption or reflectance of the hazardous wavelengths (Krinsky 1979;Kobayashi and Sakamoto 1999).…”
mentioning
confidence: 99%
“…In zooplankton, carotenoid accumulation is a highly variable trait that has been linked to photoprotection against ultraviolet radiation (UVR) in field studies comparing lakes with differential UVR exposure and in experimental studies (Hairston 1976;Moeller et al 2005;Hylander et al 2009;Rautio and Tartarotti 2010;Sommaruga 2010). The underlying mechanism ascribing astaxanthin photoprotection properties involves the quenching of singlet oxygen ( 1 O 2 ) produced during UVR exposure rather than direct absorption or reflectance of the hazardous wavelengths (Krinsky 1979;Kobayashi and Sakamoto 1999).…”
mentioning
confidence: 99%
“…The negative UVR impact on traveled distance can be explained either as an artifact of the flask depth, or as a result of activated defense and repair mechanisms, which seemingly calm down daphnids (Hylander et al, 2014). Over time, swimming behavior generally increased, which in this context could indicate successful defense mechanisms (Rautio and Tartarotti, 2010;Lushchak, 2011).…”
Section: Discussionmentioning
confidence: 99%